Secondary education teacher’s views on mixed reality in inclusive environments - Verónica Marín; Begoña E. Sampedro; Marina Morales-Diaz (Journal of New Approaches in Educational Research)
Abstract When talking about digital resources in secondary education classrooms in the 21st Century, we must mention tools such as Mixed Reality (MR). However, we must not only have in mind the perspective and training of teachers on their use, but we must consider that the ecologies of the classroom are becoming increasingly diverse, thus demanding an inclusive view of the entire teaching–learning process. The present article presents the opinions of a group of Spanish the Secondary Education teachers (N = 247), on Mixed Reality and inclusive education. Their opinion was collected through the use of a questionnaire composed of 15 items distributed into two dimensions, with 12 of them using a Likert-type response scale of 5 options. Among other aspects, the results showed that the female teachers were more prone on using MR in inclusive environments. As a conclusion, it was observed that even though the use of MR can promote inclusive education, whether or not they were more promising for their use in the learning of students with diverse disabilities, difficulties, or gifted, was dependent on the discipline of the professor (experiences and beliefs), as well as gender (views).